ANALISIS KESIAPAN GURU DALAM PEMBELAJARAN IPAS BERBASIS TRADISI DAN BUDAYA LOKAL DI SEKOLAH DASAR - Jihan Ainur Rofiqoh; Amnah Palistin; Aditya Farendra Aji Cahyono; Muhammad Imaduddin; Delia Indrawati (STKIP Subang, 2026)
This study aims to analyze teacher readiness for teaching local traditions and culture-based science and education in elementary schools. The research was conducted at SDN Kauman 1 using a qualitative case study design. The subjects were fourth-grade teachers selected purposively. Data collection techniques included observation, in-depth interviews, and documentation. The results indicate that teacher readiness for teaching local traditions and culture-based science and education is considered good. Teachers are able to integrate local culture into their learning through contextual and project-based approaches, such as introducing traditional foods, visiting gamelan production sites and tofu factories, and practicing local food processing. Local culture-based learning has been shown to increase student enthusiasm, participation, and understanding because the material is directly linked to real-world experiences in the surrounding environment. Furthermore, teachers employ differentiated learning to meet students' learning needs. However, implementation still faces several challenges, such as limited time, limited learning resources, coordination of extracurricular activities, and the need to develop local culture-based teaching modules. Therefore, support is needed in the form of strengthened lesson planning, provision of facilities, and development of teaching materials to optimize the implementation of local traditions and culture-based science and education.